1992
DOI: 10.1177/096032719201100502
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals in Human Liver

Abstract: The levels of Cr (2.49±0.89 ppm), Mn (5.08 ± 1.60 ppm), Ni (1.81±0.95 ppm) and Pb (4.43 ± 3.12 ppm) were measured in dessicated liver from 44 cases of sudden traumatic death considered as representative of the general population in our area, after ruling out the presence of any underlying disease. Atomic absorption spectrophotometry and electrothermal atomitazion was carried out after hot, acid digestion, of the dessicated samples. After cancelling the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…The lack of any Table 3. Hepatic lead concentrations in female humans relationship between the age of the deceased individual and the amount of lead found in his/her liver is consistent with the findings of Bona (1992) and Oldereid (1993). Livers from males tend to contain a higher level of lead on average than for females.…”
Section: Resultssupporting
confidence: 79%
“…The lack of any Table 3. Hepatic lead concentrations in female humans relationship between the age of the deceased individual and the amount of lead found in his/her liver is consistent with the findings of Bona (1992) and Oldereid (1993). Livers from males tend to contain a higher level of lead on average than for females.…”
Section: Resultssupporting
confidence: 79%
“…En ce qui concerne nos résultats, les concentrations obtenues sont généralement inférieures à celles publiées dans des études antérieures [8][9][10][11][12][13][14]. Compte tenu de la taille ré-duite de notre échantillon, il ne nous a pas été possible de différencier les deux sexes.…”
Section: Discussionunclassified
“…Cr(VI) is suspected of being one of initiators for lung cancer (1). Recently, it was reported that several ppm of chromium was measured in many livers following sudden traumatic death (2). Thus, interest in the possible biological function of chromium continues to increase, particularly at the trace level.…”
Section: ᭧ 1997 Academic Pressmentioning
confidence: 99%
“…Many researchers have presented the determination of chromium in biological materials by electrothermal atomic absorption spectrometry (ETAAS) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), inductively coupled plasma emission spectrometry (ICP) (17), and flame AAS (18,19), which have relatively high sensitivities and are convenient. In these methods, ETAAS has higher sensitivity but severe chemical interferences (6,16).…”
Section: ᭧ 1997 Academic Pressmentioning
confidence: 99%
See 1 more Smart Citation